Project 4 : hardware and grounding unit (HGU) - Low, Pei Hao (2016)
Water is used in every domestic households contributes to almost half the percentage of our overall water consumption in Singapore. The percentage of water usage during shoenng activity oía typical domestic household stand a relative higher as compared to rest. Whenever water heater is require to provide wami ‘ater during showeriuig event, majority would tends to step away from the water flow direction coming oLut of the shrncrhcad until water reaches desirable temperature which incur potential of precious waler wastagc This project targets to help to eliminated water wastagc during showering event by mplcmcnting an add-on Water Saving System (WSS) compatible with any existing conventional saler heater in the market, however, in this report focus more on hardware and Grounding Unit (HGU) which is one-fourth of the unit involve in the overall system for water diversion between the desirable and non-desirable water temperature as well as additional features which was included to the IIGIJ in order to improve of robustness of the WSS. The details of both researches and developing progress done to build the IIGU are covers in details under respective section of this report. This report also covers the following such as experimental tests conducted between the HOU with the three other Lunits. clcctncal wires installation of WSS simulation prototype, pali of the installation test process of the WSS, the successful overall WSS simulation prototype developed and the functional test to illustrate benefit of using this system. The WSS prototype developed was a success l this system was both nominated and exhibited during NTU Open house 2016 under School of Electrical and Electronic Engineering Final Year Project showcase for general public viewing. This system have also participated in the Switching to Suitable Solution (SSS)Case Challenge 2016 organized by Earthlunk NTU.